2022
DOI: 10.22270/jddt.v12i6.5760
|View full text |Cite
|
Sign up to set email alerts
|

A comparative pharmacodynamic and pharmacokinetic study of Vildagliptin SR 100 mg tablet in normal healthy adult male subjects

Abstract: Background: Vildagliptin, a potent dipeptidyl peptidase IV inhibitor (DPP-4i), is usually administered twice daily to provide ≥90% inhibition of DPP-4 over 24 hours. Considering most type 2 diabetes (T2D) patients are on multiple medications, reducing dosing and pill burden can increase patient convenience. A 100 mg Vildagliptin sustained release (SR) formulation that would inhibit DPP-4 ≥ 80% over 24 hours with a lower dosing frequency was developed. The study was thus conducted to evaluate the pharmacodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Similar to this, a study by Joshi et al under fasting conditions showed that vildagliptin SR 100 mg is bioequivalent to vildagliptin 50 mg and provides 80% DPP4 inhibition for 24 hours, thus improving glycemic control while decreasing the frequency of medication intake. 12 Evidence suggests that vildagliptin SR 100 mg once daily is equally efficacious and safe as vildagliptin 50 mg twice daily. The result of a randomized, open-label, phase 4 and clinical trial conducted on Indian patients showed that vildagliptin 100 mg SR once daily is equally effective as 50 mg twice daily vildagliptin in reducing HbA1C, fasting, and postprandial blood glucose levels when used along with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this, a study by Joshi et al under fasting conditions showed that vildagliptin SR 100 mg is bioequivalent to vildagliptin 50 mg and provides 80% DPP4 inhibition for 24 hours, thus improving glycemic control while decreasing the frequency of medication intake. 12 Evidence suggests that vildagliptin SR 100 mg once daily is equally efficacious and safe as vildagliptin 50 mg twice daily. The result of a randomized, open-label, phase 4 and clinical trial conducted on Indian patients showed that vildagliptin 100 mg SR once daily is equally effective as 50 mg twice daily vildagliptin in reducing HbA1C, fasting, and postprandial blood glucose levels when used along with metformin.…”
Section: Discussionmentioning
confidence: 99%